Stretchable spin valve with strain-engineered wrinkles grown on elastomeric polydimethylsiloxane. (31st December 2018) - Cheng, Wenjuan; Zhou, Zheng; Pan, Minjie; Yang, Huali; Xie, Yali; Wang, Baomin; Zhan, Qingfeng; Li, Run-Wei
Abstract: Electronics of tomorrow will be flexible, stretchable, light-weighted, wearable, and even implantable. Here, we fabricated stretchable spin-valve magnetic field sensors on the elastomeric poly(dimethylsiloxane) (PDMS) membranes with pre-strain induced wrinkles. Two in-plane patterns (linear and serpentine) were fabricated by shadow mask to investigate the shape effect on the stretchability. The linearly patterned spin valve fabricated under 50% tensile pre-strain realizes a nearly constant giant magnetoresistance (GMR) ratio of 6.3% and magnetic field sensitivity of 0.26%/Oe when repeatedly stretched up to 50%. In contrast, the serpentine spin valve grown on a pre-strained substrate experience serious cracks when releasing the pre-strain due to the Poisson effect. Nevertheless, the serpentine spin valve grown on a freestanding PDMS, i.e. without a growth pre-strain, show stable GMR performance when tensile strain up to 10% was applied. Our investigation indicates that both the out-of-plane wrinkles and the in-plane patterns are important to determine the ultra-stretchability of the shapeable magnetoelectronic devices.